Uji Daya Hambat Ekstrak Buah Kelor (Moringa oleifera Lamk) Terhadap Pertumbuhan Jamur Candida Albicans - Nuryanti, Siti; Mustapa, Kasmudin; Sudarmo, I Gede (Universitas Tadulako, 2016)
Moringa (moringa oleifera lamk) is a nutritious plant that can cure various diseases. Part of this plant such as leaves, roots, flowers, and fruits serve as a traditional medicine. The aim of this study is to determine the inhibitory of extract of moringa fruit on the growth of the fungus candida albicans. The extract of moringa fruit is made by using several solvents such as distilled water, ethanol and hexane. Suspension of the candida albicans obtained from Clinical Laboratory, Palu, Central Sulawesi. Suspension of the candida albicans is synchronized with Mc. Farland solution. The fungus test uses a pitting method. The results showed that inhibition of extract of moringa fruit on the growth of the fungus candida albicans with solvents of distilled water provides greater results as compared with ethanol and hexane. Based on the results of the observation, the percentage of inhibition of the extract of moringa fruit on the growth of the fungus candida albicans with various solvents are 100% for distilled water, 59.99% for ethanol and 6.97% for hexane. The result of phytochemical screening test showed that the moringa fruit contains alkaloids, flavonoids and steroids.